Exploring the Causal Relationship Between Economic Growth and Farmer’s Exchange Rate: Evidence from West Nusa Tenggara Province, Indonesia - Eka Putri Pratiwi; Diswandi Diswandi (Cita konsultindo, 2024)
Economic growth is influenced by various factors, including the contribution of the agricultural sector. Within the micro-analysis of this sector, the farmer's exchange rate (NTP) can impact the rate of economic growth in a region. This study analyzes the causal relationship between economic growth and NTP in West Nusa Tenggara Province, Indonesia using the Granger causality test. The findings reveal no significant causal relationship between economic growth and NTP. The study recommends further research to explore and assess other micro variables that may influence economic growth, thereby enabling policymakers to implement strategies that strengthen the agricultural sector's contribution to economic development.